INDONESIAN LANGUAGE AND LITERATURE LEARNING IMPLEMENTATION IN THE STATE JUNIOR HIGH SCHOOLS IN SURAKARTA DURING THE COVID-19 PANDEMIC - Nugraheni Eko Wardani; Sarwiji Suwandi; Titi Setiyoningsih; Chafit Ulya; Sugit Zuliyanto (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe and explain the implementation of Indonesian language and literature learning in SMP Negeri 2 Surakarta and SMP Negeri 4 Surakarta. The analysis of the learning implementation was emphasized on the analysis of learning media, learning materials, learning models and methods, and learning assessment for each school. This qualitative descriptive research method applied case study techniques. Sources of data were online learning events in both schools, teacher informants of both schools, and documents, while data collection techniques were learning observation, teacher informant interviews, and document analysis. Besides, the data validity technique was carried out by method triangulation and data source triangulation. The data were then analyzed by employing Miles and Hubermann’s flow analysis technique. The results revealed that the learning media utilized by the teachers varied, comprising WhatsApp groups, email, google classroom, google meet, zoom, YouTube, and radio. The learning materials used the Wahana Pengetahuan package book and junior high school distance Indonesian learning e-modules, PPT, teacher-made modules, etc. Both schools also used the problem-based learning model. In addition, the assessment encompassed attitude assessment, knowledge assessment, and skills assessment.